A systematic review of the safety and efficacy of mesenchymal stem cells for disc degeneration: insights and future directions for regenerative therapeutics - Yim, Rita Lok-Hay; Lee, Juliana Tsz-Yan; Bow, Cora H; Meij, Björn; Leung, Victor; Cheung, Kenneth M C; Vavken, Patrick; Samartzis, Dino (Stem cells and development, 2014)
Intervertebral disc degeneration is associated with low-back pain. Mesenchymal stem cells (MSCs) have been used to "regenerate" the disc. The aim of this study was to perform a systematic review of comparative controlled studies that have assessed the safety and efficacy of using MSCs for disc regeneration. Literature databases were extensively searched. Trial design, subject-type, MSC sources, injection method, disc assessment, outcome intervals, and complication events were assessed. Validity of each study was performed. Twenty-four animal studies were included with 20.8% of the studies reporting randomization of groups. Trials in humans fulfilling inclusion criteria were not noted. The studies represented 862 discs that were injected with MSCs and 1,603 discs as controls. All three types of MSCs (ie, bone marrow, synovial, and adipose tissues) showed successful inhibition of disc degeneration. Bone-marrow-derived MSCs demonstrated superior quality of repair compared with other non-MSC treatments. A 2.7% overall complication rate was noted, whereby complications were noted only in rabbits. Overall, evidence suggested that MSCs increased disc space height in the majority of animal models. This is the first systematic review to assess the safety and efficacy of MSCs for the treatment of disc degeneration. Short-term MSC transplantation is safe and effective; however, additional, larger, and higher-quality studies are needed to assess the long-term safety and efficacy. Inconsistencies in methodological design and outcome parameters prevent any robust conclusions. Human-based clinical trials are needed. Recommendations are further made to improve efficacy, reduce potential complications, and standardize techniques for future studies.